Effect of stadium service quality on the club value perceived by the supporter: sample of Konyaspor Büyükşehir Torku Arena - Ali Sevılmıs; Erkan Faruk Sırın (Türk Spor ve Egzersiz Dergisi)
This study, which aims at introducing the relationships between the quality perceived in stadium services and the value the supporters perceive toward the club and how much the value attributed by supporters to the sport club was affected from the stadium service quality perceived by supporters, was designed in the relational scanning model taking place in quantitative study. The data in the study were obtained 679 supporters, determined by the method of randomly sampling, coming to watch the matches of Torku Konyaspor-Akhisar Belediyespor, Torku Konyaspor-Galatasaray, Torku Konyaspor-Mersin İdman Yurdu, and Torku Konyaspor-Gençlerbirliği in the existing eight tribune areas in 2015 -2016 football season. As data collecting instrument, “Personal Information Form”, “Scale of Service Quality Perceived in Stadiums”, and “Scale of Club Values toward Supporters” were utilized. In the analysis of the data, in order to examine the relationships between the variables, correlation and regression analyses were used. As a conclusion, it was identified that stadium service quality increased the club value perceived by supporter. As a result of regression analysis made, while the linear effects of the dimensions of physical environment quality, interaction quality, and core service quality on the club value, perceived by the spectator was identified, it was found that the dimension, whose the effect of core service quality was the most, was stadium service quality.